2018
DOI: 10.3171/2016.11.jns161020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ischemic lesion prevalence after endovascular treatment of intracranial aneurysms, as documented by 3-T diffusion-weighted imaging: a 2-year, single-center cohort study

Abstract: OBJECTIVE Even though published data exist concerning the prevalence of ischemic lesions detected by diffusion-weighted imaging (DWI) following endovascular treatment of intracranial aneurysms, a single-center cross-evaluation of the different endovascular techniques has been lacking. The authors sought to prospectively evaluate the prevalence and clinical significance of ischemic lesions occurring after endovascular treatment of intracranial aneurysms and to compare the safety and effectiveness of a broad spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Interestingly, all three patients who were treated with flow diverters in our study had at least one post-procedure DWI lesion while only one patient out of four who was treated with coiling alone had two DWI lesions. These findings are: (a) consistent with recent meta-analysis findings 25 that demonstrated a significantly higher rate of DWI-positive lesions following endovascular flow diversion compared with coiling alone, possibly due to the high ratio of metal coverage in flow diverters that might increase the risk of intra-luminal thrombosis; (b) in contrary to most previous studies 25,28,29 that reported a higher occurrence rate of DWI lesions after endovascular coiling. The low rate of DWI lesions on post-procedure MRI in our patients who were treated with coiling is interesting because it might shed new light on the possible potential neuroprotective benefits of RIPC for the prevention and treatment of stroke in patients who are at high risk of ischemic events.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, all three patients who were treated with flow diverters in our study had at least one post-procedure DWI lesion while only one patient out of four who was treated with coiling alone had two DWI lesions. These findings are: (a) consistent with recent meta-analysis findings 25 that demonstrated a significantly higher rate of DWI-positive lesions following endovascular flow diversion compared with coiling alone, possibly due to the high ratio of metal coverage in flow diverters that might increase the risk of intra-luminal thrombosis; (b) in contrary to most previous studies 25,28,29 that reported a higher occurrence rate of DWI lesions after endovascular coiling. The low rate of DWI lesions on post-procedure MRI in our patients who were treated with coiling is interesting because it might shed new light on the possible potential neuroprotective benefits of RIPC for the prevention and treatment of stroke in patients who are at high risk of ischemic events.…”
Section: Discussionsupporting
confidence: 89%
“…In the systemic review and meta-analysis by Bond et al , the rate of postprocedural DWI documented ischemic lesions was 45%, 44%, 43%, and 67% after simple coiling, balloon assisted coiling, stent assisted coiling, and flow diversion, respectively 23. Single center studies evaluating silent cerebral ischemia after intracranial aneurysm treatment with the PED reported an asymptomatic cerebral ischemia rate of 50.9–90% 4–11. These studies reported an increased risk of post-PED treatment silent cerebral ischemia with female gender,4 aneurysm size ≥10 mm,5 and age ≥60 6…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that management of intracranial aneurysms with the PED-Shield is associated with a lower rate of postprocedural, diffusion weighted imaging (DWI) documented cerebral ischemia than previously reported with the PED 4–11. Hence the purpose of this prospective study was to determine the incidence of cerebral ischemia on postprocedural DWI following PED-Shield treatment of intracranial aneurysms in a single institution cohort of consecutive patients.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Albayram et al demonstrated that the risk of thromboembolic events resulting in DWI lesions was not more significant when BACE was used compared with CE 26. In a recent study evaluating the presence of ischemic lesions following endovascular treatment of aneurysms using 3 T DWI, Iosif et al found that the rates of occurrence of new DWI positive lesions were higher for CE and stent assisted coil embolization (SACE) compared with BACE (64.3% for CE, 61.1% for SACE, and 54.5% for BACE) 27. It is not clear if subarachnoid hemorrhage increases the risk of thromboembolic events during BACE due to its prothrombotic milieu.…”
Section: Discussionmentioning
confidence: 99%